Implementasi Teknik Sinematografi dan Color Grading dalam Film Pendek “Demi Cinta” - Ester Theressa Hutagalung; Muchamad Zainul Rohman; Yusni Nyura (CV MEDAN TEKNO SOLUSI, 2025)
Health is a highly valued condition for every individual and society. Health not only refers to the absence of disease or disability, but also includes optimal physical, mental and social well-being. Health is often overlooked in the routine of daily life where many individuals are too focused on the demands of work to earn a great income. Short films have the potential to deliver messages about the importance of prioritizing health. The purpose of this research is to create aesthetic shooting and improve image quality through Cinematography and Color Grading techniques. The use of Cinematography Techniques is applied to the filmmaking process at the pre-production, production and post-production stages. Cinematography techniques include the 5'C principle, namely camera angle, close up/shot size, compositions, continuity, and cutting/editing. The use of Color Grading in a film to adjust colors and tones consistently to achieve the desired visual mood, strengthen the atmosphere of the story, and express character emotions and Adobe Premiere Pro as an application used to edit videos. This research produces a short film that applies Cinematography and Color Grading Techniques with the title